2018
DOI: 10.1007/s00426-018-0995-6
|View full text |Cite
|
Sign up to set email alerts
|

Do arousal and valence have separable influences on attention across time?

Abstract: Previous research has shown that emotions differentially influence attention across time, especially when the valence of the attended stimuli is congruent with the emotion of observer. Sadness produces a larger attentional blink while fear and happiness produce smaller attentional blinks. We report on four dual-task rapid serial visual presentation experiments in which participant emotion and the affective features of the first target (T1) were systematically varied to determine whether arousal and valence hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…However, given the substantial amount of heterogeneity in the results we additionally explored the potentially moderating effects of emotion-type (fear, anger, sad, happy) and WM task load. Differential influences of emotion-type might partially account for the heterogeneity in the results because threat-related stimuli might be more arousing, and thus impact WM, more compared with sadness-related stimuli (Saxton, Myhre, Siyaguna, & Rokke, 2018; Vuilleumier, 2002). The rationale for WM load as an additional moderator is that it has been shown to influence attentional control (Lavie, Hirst, de Fockert, & Viding, 2004).…”
Section: Results Of the Behavioral Meta-analysismentioning
confidence: 99%
“…However, given the substantial amount of heterogeneity in the results we additionally explored the potentially moderating effects of emotion-type (fear, anger, sad, happy) and WM task load. Differential influences of emotion-type might partially account for the heterogeneity in the results because threat-related stimuli might be more arousing, and thus impact WM, more compared with sadness-related stimuli (Saxton, Myhre, Siyaguna, & Rokke, 2018; Vuilleumier, 2002). The rationale for WM load as an additional moderator is that it has been shown to influence attentional control (Lavie, Hirst, de Fockert, & Viding, 2004).…”
Section: Results Of the Behavioral Meta-analysismentioning
confidence: 99%
“…Fortunately, recent investigations adopting several paradigms, such as the rapid serial visual presentation (RSVP) procedure, the oddball task, and the emotional timeout procedure, have shown that stimulus emotionality does have an influence (Clewett et al, 2017;Dunsmoor et al, 2015;Sakaki et al, 2014;Saxton et al, 2018;Schmidt & Schmidt, 2016).…”
Section: Collaborative Memory For Emotional Stimuli and The Emotional...mentioning
confidence: 99%
“…However, given the substantial amount of heterogeneity in the results we additionally explored the potentially moderating effects of emotion-type (fear, anger, sad, happy) and WM task load. Differential influences of emotion-type might partially account for the heterogeneity in the results because threat-related stimuli might be more arousing, and thus impact WM, more compared to sadness-related stimuli (Saxton, Myhre, Siyaguna & Rokke, 2018;Vuilleumier, 2002). The rationale for WM load as an additional moderator is that it has been shown to influence attentional control (Lavie, Hirst, de Fockert & Viding, 2004 = .004.…”
Section: Overall Effect Of Affective Context On Wm In Psychologicallymentioning
confidence: 99%